2005
DOI: 10.1529/biophysj.105.059667
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Ligation in Photosystem II under Inhibiting Conditions

Abstract: In oxygenic photosynthesis, PSII carries out the oxidation of water and reduction of plastoquinone. The product of water oxidation is molecular oxygen. The water splitting complex is located on the lumenal side of the PSII reaction center and contains manganese, calcium, and chloride. Four sequential photooxidation reactions are required to generate oxygen from water; the five sequentially oxidized forms of the water splitting complex are known as the Sn states, where n refers to the number of oxidizing equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 63 publications
5
31
1
Order By: Relevance
“…For example, our measurements are on a much faster time scale compared with rapid-scan Fourier-transform IR (FT-IR) studies of the OEC (for examples, see refs, [40][41][42]. Note that it has recently been suggested that a histidine perturbation may occur with S state cycling on the 10-s time scale (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our measurements are on a much faster time scale compared with rapid-scan Fourier-transform IR (FT-IR) studies of the OEC (for examples, see refs, [40][41][42]. Note that it has recently been suggested that a histidine perturbation may occur with S state cycling on the 10-s time scale (43).…”
Section: Discussionmentioning
confidence: 99%
“…The IR cell was assembled by using another calcium fluoride window and a 25-m spacer. The 25-m path length spacer was greased, and the sample was sealed with vacuum grease and parafilm to prevent dehydration during the experiment (42,49). A continuous-wave diode laser (Ekips Technology, Norman, OK) emitting at 1,483 cm Ϫ1 was used as the probe, a Q-switched Nd:YAG (neodymium:yttrium aluminum garnet) laser (Spectra-Physics) was used to produce a 532-nm photolysis pulse, and the transient absorbance of the probe was detected with a liquid nitrogen-cooled mercurycadmium-telluride detector.…”
Section: Methodsmentioning
confidence: 99%
“…Reaction-induced FT-IR difference spectroscopy was performed at 263 K and pH 7.5, and in the presence of 7 mM potassium ferricyanide, as previously described (17,(46)(47)(48). The resuspended sample, described above, was thawed and pelleted.…”
Section: Methodsmentioning
confidence: 99%
“…On the assumption that Ca 2+ had been removed from its binding site without the use of a chelator, the modified spectral properties of the S 2 state have been attributed to binding of the chelator to the Ca 2+ -depleted Mn cluster (Boussac et al 1990;Kimura and Ono 2001). However, the implication that without chelator the Ca 2+ -free S 2 state would not be modified seems at odds with the fact that even replacement of Ca 2+ by Sr 2+ , which is so similar to Ca 2+ that it supports O 2 evolution, clearly modifies the EPR (Boussac and Rutherford 1988b) and FTIR (Barry et al 2005;DeRiso et al 2006) spectral properties of the S 2 state. Therefore, we prefer the direct interpretation that chelators prevent rebinding of Ca 2+ after NaCl/light treatment.…”
Section: Ca 2+ Depletion Methods Revisitedmentioning
confidence: 99%